[OP.1B.02] SERUM URIC ACID AND BLOOD PRESSURE IN EUROPEAN RURAL POPULATION WITH NORMAL KIDNEY FUNCTION. DATA FROM BRISGHELLA HEART STUDY (ITALY) AND ENAH STUDY (CROATIA). (September 2016) - Karanovic, S.; Ivkovic, V.; Parini, A.; Vrdoljak, A.; Abramovic-Baric, M.; Bacchelli, S.; Cagnati, M.; Francesco, A.; Cicero, A.F.G.; D'Addato, S.; Esposti, D. Degli; Fucek, M.; et al.
Abstract : Objective: An elevated serum uric acid (SUA) was observed in patients with primary hypertension (HT) and prehypertension (PHT). SUA was associated with blood pressure (BP) values in general population starting from childhood, while treatment with xanthine oxidase inhinitors (XOi) proved to decrease BP indicating on causative role of SUA on development of HT. As data for European, particularly rural, population is lacking our aim was to analyze association of SUA with BP in two rural areas in Croatia and Italy. Design and method: In this international prospective long-term follow up study data on 5162 subjects from BrEna cohort formed from original cohorts of Brisighella Heart Study (Italy) and ENAH study (Croatia) were analysed. Out of them 1596 (754 m 842 w) were eligible for further analyses. Subjects treated with antihypertensive drugs and XOi were excluded. There were 139 subjects with PHT (high normal BP). Subjects with diabetes, eGFR <60 ml/min (MDRD equation), XOi and antihypertensive therapy were exluded. Results: Significant trend in SUA was observed across BP categories NT, PHT and HT (276 (IQ 228–330) vs. 294 (IQ 240–342) vs. 307 (IQ252–360) (p for trend <0.001). Significant correlations of SUA with systolic and diastolic BP were observed (r = 0.192; p < 0.001, r = 0.08; p < 0.001). In mulitvariate linear regression analyses SUA was independently associated with systolic BP after adjustment for age, gender, waist circumference, HDL, LDL, TG, eGFR (beta = 0.11 p < 0.001), each increase of 100 umol/l SUA increase systolic BP for 2.8 mmHg. In adjusted multivariate logistic regression analyses SUA was an independent predictor for HT, i.e. subjects in 4th Q of SUA had higher risk for being HT (1.9 [1.2–3.0]), but not for being PHT. Conclusions: In European rural population without CKD and diabetes SUA is associated with BP and is an independent predictor for HT, but not for PHT. Our results are in agreement with vast majority surveys pointing on possible causative role which should be evaluated in prospective study.